Exploring Dynamics in Post-stroke Motor Rehabilitation: A Systematic Review of Implementation Barriers and Facilitators using the COM-B Model. - Yang, Chang; Li, Changxiu; Chen, Wei; Lin, Jian; He, Yunsi; Zhang, Qi (NeuroRehabilitation, 2025)
Purpose: This systematic review aimed to identify barriers and facilitators in post-stroke motor rehabilitation across patient, caregiver, and healthcare professional levels, employing the capability, opportunity, motivation, behavior (COM-B) model and the theoretical domains framework (TDF). Materials and Methods: A systematic search of PubMed, EMBASE, Cochrane Library, Web of Science, and CINAHL, following PRISMA guidelines, covered literature until January 20, 2025. Studies reporting qualitative, quantitative, or mixed-methods data on post-stroke motor rehabilitation barriers and facilitators were included. Quality assessment utilized MMAT 2018. Results: Analyzing 48 studies, we found that barriers to post-stroke motor rehabilitation encompassed motor impairments, cognitive issues, resource scarcity, and environmental factors, while facilitators included good physical abilities, resource accessibility, and social support. The COM-B model elucidated the dynamic interplay between capability, opportunity, and motivation, suggesting educational interventions and telerehabilitation as avenues for improvement. Conclusion: This systematic review, guided by the COM-B model, identifies key barriers and facilitators in post-stroke motor rehabilitation. It emphasizes the importance of targeted education, improved telerehabilitation infrastructure, and robust social support systems to address multifaceted challenges.